Sex-Based Differences in Diabetes Prevalence and Risk Factors: A Population-Based Cross-Sectional Study Among Low-Income Adults in China - Zhang, Hongyan; Ni, Jingxian; Yu, Changshen; Wu, Yanan; Li, Jingyan; Liu, Jie; Tu, Jun; Ning, Xianjia; He, Qing; Wang, Jinghua (Frontiers in Endocrinology, 2019)
Aims: The prevalence of diabetes mellitus (DM) among adults has reached epidemic proportions worldwide, including China. In China, sex-based differences in the prevalence and risk factors of DM may exist, particularly among low-income individuals. Thus, we assessed these differences in the prevalence of DM and its risk factors in a low-income Chinese population. Materials and Methods: Residents aged ≥45 years without histories of strokes or cardiovascular disease were recruited for this study. Multivariate logistic regression analyses were performed to assess the association of risk factors with DM prevalence. Results: This study included 3725 participants (41.2%, men; 58.8%, women). The mean age of the women (61.1 years) was higher than that of the men (59.14 years, P < 0.001). There was no significant sex-based difference in DM prevalence (men, 14.1%; women, 14.5%). Overweight, obesity, high triglyceride levels, and hypertension were independent risk factors for DM in both sexes. However, high-density lipoprotein-cholesterol levels were negatively associated with DM risk among men (odds ratio [OR], 0.544; 95% confidence interval [CI], 0.355–0.833; P = 0.005). Among women, advanced age and high low-density lipoprotein-cholesterol levels were independent risk factors for DM; there was a higher DM risk for women aged 55–74 years than for those aged 45–54 years; however, physical activity was associated with an increased risk of DM (OR, 1.705; 95% CI, 1.195–2.432; P = 0.003). Conclusions: These findings suggest a crucial need to implement individualized blood pressure, weight, and lipid managements in low-income populations in China to reduce the burden of DM, especially among older women.